Features of Fixing the Folklore of Peoples of Yakutia (1930-1970): the Method of Selecting Informants according to G. U. Ergis - Olga I. Charina; Anna S. Larionova; Valentina A. Petrova (Научный диалог)
Methods and approaches in the selection of informants for fixing folklore works of Russians, Evens, Yakuts, who have inhabited the North-East of Yakutia since ancient times, are considered. The authors dwell on such issues as ways of finding informants; clarification of the status (narrator, singer and performer); concretization of the performer’s personality and his repertoire. The novelty of the research is seen in the fact that at the present stage, methods of selecting informants are being studied; the approaches to the selection of performers of song folklore, used by M.N.Zhirkov, are specified; the change in the status of the storytellers of Russian folklore is traced; the main features of the performance of the Even epic by the narrators are analyzed. The relevance of the research is due to the fact that the history of the study of the epic and song heritage of personalities-performers of the song-prose epic of the Russians Ustye, Evens and Yakuts by the staff of the Institute of Language and Culture is examined. Methods and approaches of M. N. Zhirkov in the selection of performers, as well as their repertoire to be fixed, are revealed. The importance of summarizing the already achieved results and setting new tasks in collecting and fixing folklore and musical material in the context of the extinction of folklore tradition and a reduction in the number of experts of traditional culture is affirmed.